Oprogramowanie open source jako alternatywa dla projektów komercyjnych - Nojszewski, Dariusz; Rubach, Paweł (Open Source Software : an Alternative Solution, 2005)
As a result of the growing popularity open source software becomes a strong competitor for commercial products. This paper underlines the importance and popularity of this kind of software and outlines a number of successful examples of open source projects, which are regarded as alternative or as in case of the Apache web server the de facto standard in many deployments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 379-387